2008
DOI: 10.4088/jcp.08m04011
|View full text |Cite
|
Sign up to set email alerts
|

Depression Precipitated by Alcohol Use in Patients With Co-Occurring Bipolar and Substance Use Disorders

Abstract: Objective Bipolar disorder (BD) and substance use disorders (SUDs) frequently co-occur. However, little is known about the near-term effects of substance use on BD. Thus the present study tests whether alcohol use precipitates depression among patients with co-occurring BD and SUD. Method This study uses data collected as part of two clinical trials of a manualized group therapy for patients with co-occurring bipolar disorder and substance dependence. One hundred fifteen participants were assessed at baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
4
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 20 publications
(30 reference statements)
3
28
4
1
Order By: Relevance
“…In fact, in our study 
we found that they differ for predominant polarity. The depressive prevalent polarity we found in BD patients with AUD is in line with the previously observed association between alcohol abuse and increased frequency of depressive episodes in BD [12, 23]. Accordingly, this finding may 
also be consistent with the decrease in alcohol abuse longitudinally observed in a group with manic predominant polarity [11].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, in our study 
we found that they differ for predominant polarity. The depressive prevalent polarity we found in BD patients with AUD is in line with the previously observed association between alcohol abuse and increased frequency of depressive episodes in BD [12, 23]. Accordingly, this finding may 
also be consistent with the decrease in alcohol abuse longitudinally observed in a group with manic predominant polarity [11].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, a recent prospective study found a significant longitudinal decrease of alcohol/
other drug abuse during the course of the illness in the manic predominant polarity group [11]. Moreover, another study found increased frequency of depressive episodes in patients with comorbid BD and AUD [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Similarly to our findings among homeless populations, substance use is particularly common in those suffering from BD (Merikangas et al, 2008), and it has been associated with bipolarity in both full-blown expressions (Albanese et al, 2006;Bacciardi et al, 2013;Cassidy et al, 2001;Do and Mezuk, 2013;Elbogen and Johnson, 2009;Jaffee et al, 2009;Maremmani et al, 2008;Maremmani et al, 2006;Mitchell et al, 2007) and temperamental expressions Pacini et al, 2009). Individuals with mania are 8.4 times more likely to experience lifetime drug dependence as compared to the general population (Do and Mezuk, 2013).…”
Section: Substance Use and Bipolar Disordersupporting
confidence: 83%
“…However, in persons for whom bipolar disorder symptoms were resolved with mood-stabilizing medications, or symptoms of major depression with antidepressants, substance use typically was not affected by the medication, alcohol or drug use continued. Sometimes this affected recovery from the mood disorder (35), and in other cases it did not (36,37).…”
Section: Discussionmentioning
confidence: 99%